Economics as Religion and Christianity as oikonomia: Giorgio Agamben and the Homo Sacer - Gaël Giraud (Religions, 2023)
Among the contemporary thinkers who try to think of economics not just as having a non-empty intersection with religion but as being intrinsically religious, Giorgio Agamben occupies a singular place. Indeed, one of the main theses of his major work, Homo Sacer, is that the modern rupture between “sovereignty” and “government”—which lies at the heart of his political diagnosis of our contemporary situation—can be traced back to classical Trinitarian theology. Since this rupture is allegedly responsible for today’s Western understanding of economics, this implies that, according to the Italian philosopher, our current crisis has Christian theological roots. In this paper, I first discuss the argument put forward by Agamben to assert that, at least since the Trinitarian controversies of the second century, Christianity has become intrinsically oikonomia, that is, it understands history as the unfolding of a providential dynamic which, he claims, anticipates today’s celebrated “invisible hand” of decentralized markets. Next, I offer critical reflections upon this argument by questioning whether contemporary mainstream economics can be reduced to the “market fundamentalism” with which it is often confused. The article concludes by questioning, in turn, whether all Christian traditions boil down to the historical trend that Agamben characterizes as leading to today’s problematic mainstream economics.